In-work transfers in good times and bad: simulations for Ireland - Olivier Bargain; Karina Doorley (Institute for the Study of Labor (IZA), 2009)
In-work transfers are often seen as a good trade-off between redistribution and efficiency, as they alleviate poverty among low-wage households while increasing financial incentives to work. The present study explores the consequences of extending these transfers in Ireland, where support for low-wage households has been of limited scope. The employment and poverty effects of alternative policies are analyzed thanks to counterfactual simulations built using a micro-simulation model, the Living in Ireland Survey 2001 and labour supply estimations. Firstly, we study the effect of recent extensions of the existing scheme, the Family Income Supplement (FIS), and of its replacement by the refundable tax credit in force in the UK. Secondly, little is known about the impact of macro-level changes on the distribution of resources at the household level, which is particularly relevant in a country deeply affected by the current economic downturn. We suggest a preliminary analysis of the capacity of alternative in-work transfer scenarios to cushion the negative impact of earnings losses and cuts in the minimum wage.
Keywords: C25; C52; H31; J22; 330; Microsimulation; working poor; welfare; labour supply; take-up; Negative Einkommensteuer; Aktivierende Sozialhilfe; Sozialreform; Wirkungsanalyse; Arbeitsangebot; Armut; Mikrosimulation; Irland